The Shiloh campaign - Woodworth, Steven E. (Civil War campaigns in the heartland., 2009)
This title provides new insights into the civil War's bloodiest battle. Steven E. Woodworth has brought together a group of historians to reassess this significant battle and provide in-depth analysis of key aspects of the campaign and its aftermath.